Petrology and geochemistry of Variscan dykes from the Jachymov (Joachimsthal) ore district, Czech Republic - Stemprok,M.; Seifert,T.; Holub,F.V.; Chlupacova,M.; Dolejs,D.; Novak,J.K.; Pivec,E.; Lang,M. (Journal of Geosciences, 2008)
Mafic and silicic dyke rocks, which occur in the Ag-U ore district of Jachymov (Joachimsthal) in the Krusne hory (Erzgebirge) belong to kersantites, diorite porphyries, and granite porphyries, subordinately to spessartites. Dykes of minettes are located outside the district and penetrate the Nejdek-Eibenstock granitic massif. Mafic and silicic dykes exhibit diverse cross-cutting relationships and form in places composite dykes. Lamprophyres correspond to shoshonitic magmas with high abundances of compatible (Cr, Ni) and incompatible elements (Rb, Ba, P). All mafic dykes were affected by a postmagmatic alteration manifested by replacement of primary olivine and pyroxenes by amphibole, biotite and chlorite. Granite porphyries crystallized from leucocratic, weakly peraluminous, low-P magmas with moderate enrichments in Rb and depletions in Ca, Sr and Zr. By contrast, diorite porphyries are intermediate rocks containing 62-65 wt. % SiO2 whose geological occurrence and major-element composition suggest origin by magma mixing involving lamprophyric and silicic melts, with simultaneous fractionation of biotite. The Th/U ratios in all dyke rocks correspond to chondritic and crustal values and demonstrate that whole-rock uranium contents were neither significantly increased nor affected by contemporaneous mineralization events.The stable isotope composition has been determined for whole rocks (O, C, S) and carbonate minerals (C, O). Wholerock δ18O values range between 1.6 to 7.8 ‰ SMOW and do not show any systematic variations with the rock types. The isotopic composition of carbonates is represented by the following values: δ18O = 19.6 to 25.0 ‰ SMOW and δ13C = -5.7 to -9.0 ‰ PDB. The high positive values of δ18O of carbonates are in a remarkable contrast to compositions of primary magmatic carbonates and indicate the carbonate formation during low-temperature hydrothermal event(s). Sulphides in kersantites and diorite porphyries yielded δ34S = 0.5 to 6.6 ‰ CDT, which document crustal in addition to mantle source of sulphur consistent with average value in the Saxothuringian crust (~ 5 ‰ CDT). Bulk magnetic susceptibility of dyke rocks shows a general decrease from mafic to silicic magmas in a sequence as follows: kersantites - 500, minettes - 350, diorite porphyries - 350 and granite porphyries - 50∙10-6 [SI]. Local increases up to 5000∙10-6 [SI] are due to accessory pyrrhotite in kersantites and diorite porphyries. Mafic dykes in the Western Krusne hory (Erzgebirge) are preferentially found within the Jachymov-Gera tectonic zone and demonstrate spatial focusing of ascending mantle-derived melts. Such pathways may have served for transfer of ore-forming elements on the crustal scale by fluids of diverse origin.
Keywords: lamprophyre; granite porphyry; uranium mineralization; magma mixing; Western Krusne hory/Erzgebirge Pluton